PANTOJA, Mariana Ciavatta. Os Milton: cem anos de história nos seringais. - Leal, Natacha Simei (Revista de Antropologia, 2013)
PANTOJA, Mariana Ciavatta. Os Milton: cem anos de história nos seringais.